Discharged but not dissatisfied: outcomes and satisfaction of patients discharged from the Edinburgh Trauma Triage Clinic. (July 2018) - Mackenzie, S. P.; Carter, T. H.; Jefferies, J. G.; Wilby, J. B. J.; Hall, P.; Duckworth, A. D.; Keating, J. F.; White, T. O.
Abstract : Aims: The Edinburgh Trauma Triage Clinic (TTC) streamlines outpatient care through consultant-led 'virtual' triage of referrals and the direct discharge of minor fractures from the Emergency Department. We compared the patient outcomes for simple fractures of the radial head, little finger metacarpal, and fifth metatarsal before and after the implementation of the TTC. Patients and Methods: A total of 628 patients who had sustained these injuries over a one-year period were identified. There were 337 patients in the pre-TTC group and 289 in the post-TTC group. The Disabilities of the Arm, Shoulder and Hand Score (QuickDASH) or Foot and Ankle Disability Index (FADI), EuroQol-5D (EQ-5D), visual analogue scale (VAS) pain score, satisfaction rates, and return to work/sport were assessed six months post-injury. The development of late complications was excluded by an electronic record evaluation at three years post-injury. A cost analysis was performed. Results: Outcomes were as good or better post-TTC, compared with pre-TTC scores. At three years, the pre-TTC group required a total of 496 fracture clinic appointments compared with 61 in the post-TTC group. Mean cost per patient was nearly fourfold less after the commencement of the TTC. Conclusion: Management of minor fractures through the Edinburgh TTC results in clinical outcomes that are comparable with the previous system of routine face-to-face consultation. Outpatient workload for these injures was reduced by 88%. Cite this article: Bone Joint J 2018;100-B:959–65.